2017
DOI: 10.1038/s41598-017-14446-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of 14-dehydroergosterol as a novel anti-inflammatory compound inducing tolerogenic dendritic cells

Abstract: Tolerogenic dendritic cells (DCs) have the ability to induce regulatory T cells and play an important role in preventing chronic inflammatory and autoimmune diseases. We have identified a novel compound, 14-dehydroergosterol, from Koji, a Japanese traditional food material fermented with fungi. 14-dehydroergosterol is an ergosterol analogue with a conjugated double bond, but the activity of 14-dehydroergosterol is much higher than that of ergosterol. 14-dehydroergosterol induces the conversion of murine bone m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The cultivated fungus body of Aspergillus kawachii was first extracted with 59% ethanol; then, rapeseed oil was added, and the oil fraction was collected as Koji extract. The concentration of 14-DHE in the Koji extract was determined by high-performance liquid chromatography (Shimadzu, Kyoto, Japan) using a C30-UG-5 column (Develosil, 10 mm × 250 mm; Nomura Chemical Co. Ltd., Aichi, Japan) with an acetonitrile–isopropanol (99:1) gradient as described by Ano et al 21 The nutritional content of this sample was: energy, 1.8 kcal; lipids, 0.2 g; and carbohydrate, protein, alcohol, moisture, and ash, 0 g per capsule.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The cultivated fungus body of Aspergillus kawachii was first extracted with 59% ethanol; then, rapeseed oil was added, and the oil fraction was collected as Koji extract. The concentration of 14-DHE in the Koji extract was determined by high-performance liquid chromatography (Shimadzu, Kyoto, Japan) using a C30-UG-5 column (Develosil, 10 mm × 250 mm; Nomura Chemical Co. Ltd., Aichi, Japan) with an acetonitrile–isopropanol (99:1) gradient as described by Ano et al 21 The nutritional content of this sample was: energy, 1.8 kcal; lipids, 0.2 g; and carbohydrate, protein, alcohol, moisture, and ash, 0 g per capsule.…”
Section: Methodsmentioning
confidence: 99%
“…In a previous study, injection of 14-DHE in mice significantly improved the clinical score and inflammatory response in a model of multiple sclerosis (experimental autoimmune encephalopathy). 20 , 21 Additionally, 14-DHE suppressed the inflammatory phenotype in dendritic cells derived from human peripheral blood mononuclear cells in response to lipopolysaccharide and interferon-γ stimulation. 21 Furthermore, 14-DHE has been shown in vitro to protect keratinocytes against UVA radiation.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…It was found that Aspergillus luchuensis mut. kawachii produces 14-dehydroergosterol ( Figure 11 ) as an anti-inflammatory substance that induces tolerogenic dendritic cells [ 82 ]. Moreover, koji extract containing 14-dehydroergosterol produced by Aspergillus luchuensis mut.…”
Section: 14-dehydroergosterolmentioning
confidence: 99%